(untitled) (Cambridge, 1990)
The final volume discusses the institutions that affected social conditions and influenced values and attitudes. Social policies were made for the most part by the comfortably off and those in power for the supposed good of the less fortunate. Contributors to this volume examine these initiatives with regard to, among others, the development of health care, philanthropy and the voluntary sector, the police and crime, professional associations and unions.
Keywords: Social institutions,Associations, institutions, etc.,Tổ chức xã hội,Hiệp hội, tổ chức...; History,History,Lịch sử,Lịch sử; Great Britain,Great Britain,Anh quốc,Anh quốc